Are jobs available in the market? a perspective from the supply side - Jamaludin, Salwaty; Said, Rusmawati; Ismail, Normaz Wana; Mohamed Nor, Norashidah (Multidisciplinary Digital Publishing Institute, 2021)
Graduate unemployment exhibits a clear increasing global trend, and Malaysia is no exception. The unemployment rate among graduates is witnessing a considerable upsurge, growing from 43,800 in 2000 (15% of total unemployed) to more than 175,500 in 2017 (35%). Numerous programmes have been implemented in order to secure jobs for the unemployed in the labour market; however, the number of unemployed graduates keeps on increasing. It is significant to recognise the main reason behind this issue to tackle the risk of long-term unemployment, specifically from the supply side. Using the Relative Importance Index (RII), this study investigated 402 respondents at selected job fairs to identify the cause of their difficulty in entering the labour market. The findings revealed that the unemployed people believe that the principal cause of their unemployment is the lack of suitable jobs for them in the market. This circumstance sends a signal of asymmetric information between demand and supply in the labour market, especially to young graduates.